Hodnocení finanční situace podniku a návrhy na její zlepšení - Tučková, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Diplomová práce se zabývá hodnocením finanční situace podniku, který se zaměřuje na výrobu gumárenských výrobků a technických pěn. Posuzovaným obdobím je rozmezí let 2010 – 2014. V teoretické části jsou vymezeny základní ukazatele, pojmy a metody finanční analýzy, které jsou využity v praktické části práce. Praktická část obsahuje základní informace o společnosti a výpočty finančních ukazatelů. Na základě zhodnocení finanční situace podniku získaných z výsledků finanční analýzy jsou prezentovány možnosti návrhů a doporučení, které by měly vést ke zlepšení hospodaření podniku

This diploma thesis deals with an evaluation of the financial situation of the company, which focuses on manufacturing rubber products and technical foams. Assessment period is between 2010 - 2014. In the theoretical part the basic indicators, concepts and methods of financial analysis, which are used in the practical part. The practical part contains basic information about the company and the calculations of financial indicators. Based on the evaluation of the financial situation of the company derived from the results of the financial analysis are presented possibilities proposals and recommendations, which should lead to improved management of the company.
Evaluation of the Financial Situation of the Company and Proposals to its Improvement
Keywords: Finanční analýza; výkaz zisků a ztrát; rozvaha; cash flow; poměroví ukazatelé; absolutní ukazatelé; soustavy ukazatelů; návrhy na zlepšení; Financial analysis; statement of comprehensive income; statement of financial positron; cash-flow; relativ indicators; absolute indicators; systems of indicators; suggestions for improvement